2020
DOI: 10.1159/000509981
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Treatment of Tinnitus during Sleep Using Combined Tinnitus Signal and Music

Abstract: Introduction: Tinnitus is a widely seen otological symptom that interferes with daily activities and causes discomfort. Tinnitus treatments can be classified into 4 main groups: pharmacological treatments, cognitive and behavioral therapy, psychological treatments, and combined treatment approaches made up of at least 2 of these 3 treatment methods. Objective: The aim of this study was to assess whether it would be possible to develop an individualized treatment method of tinnitus by application of a combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…For THI, the mean difference score between the pre-and post-treatment was available for thirteen trials. [13,15,16,18,[23][24][25][26][27][28][29][30][31] A random-effect model was used to analyze the data (I 2 = 73.8% > 50%, P = .000 < .1). Compared with before treatment, music therapy significantly reduces the THI score (SMD = −0.88, 95%CI −1.15 to −0.6, P = .000 < .001) (Fig.…”
Section: Meta-analysis Of the Effect Of Music Therapy On Severity Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For THI, the mean difference score between the pre-and post-treatment was available for thirteen trials. [13,15,16,18,[23][24][25][26][27][28][29][30][31] A random-effect model was used to analyze the data (I 2 = 73.8% > 50%, P = .000 < .1). Compared with before treatment, music therapy significantly reduces the THI score (SMD = −0.88, 95%CI −1.15 to −0.6, P = .000 < .001) (Fig.…”
Section: Meta-analysis Of the Effect Of Music Therapy On Severity Of ...mentioning
confidence: 99%
“…The TMNMT was reported in 9 articles. [15,16,23,[26][27][28][29][30][31] A random-effect model was used to analyze the data (I 2 = 61% > 50%, P = .009 < .1). TMNMT significantly decreases tinnitus scores.…”
Section: Tailor-made Notched Music Trainingmentioning
confidence: 99%
“…Tinnitus is also one of the common concomitant symptoms of SSH, with an incidence of 78.2-91.0%; some SSH patients have their hearing recovered or improved after treatment, but the tinnitus still exists for a long time or intermittently, which seriously disturbs the work and life of the SSH patients [ 4 ]. Recent studies have shown that tinnitus patients with a shorter course are more affected by tinnitus than those with a longer course, which may be related to the patient's adaptation to tinnitus [ 5 ].…”
Section: Introductionmentioning
confidence: 99%